2021
DOI: 10.4103/jfmpc.jfmpc_317_21
|View full text |Cite
|
Sign up to set email alerts
|

Level of participation in public health volunteering and its determinants among ministry of health primary health care workers in Jeddah 2019

Abstract: Context: Volunteering is an important practice for health care systems globally and contributes to the development of health care services as well. Aims: To estimate the level of participation in public health volunteering and its determinants among healthcare workers in ministry of health primary care sector, Jeddah. Settings and Design: A randomized quantitative cross-sectional self-administered survey involving all primary healthcare worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although no significant association between the sex of the physician and knowledge score was seen in this study, such an association was reported in the literature. 14,15 Here, we found that female physicians tend to recommend using soap-free cleansers more than males and refer fewer cases of atopic dermatitis to dermatologists.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although no significant association between the sex of the physician and knowledge score was seen in this study, such an association was reported in the literature. 14,15 Here, we found that female physicians tend to recommend using soap-free cleansers more than males and refer fewer cases of atopic dermatitis to dermatologists.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, young physicians and physicians with fewer years in practice had higher knowledge scores in atopic dermatitis. 14,15 These findings could be attributed to recent exposure to a structured training program in dermatological diseases during residency or medical school periods. Having structured training in dermatology was found to be associated with a better understanding of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 19 21 22 ] A previous study in Jeddah, Saudi Arabia, among medical graduates found that factors related to values and social responsibility were predictive of volunteering, whereas factors related to career development were not. [ 23 ] Our study expanded these findings to medical students, dental students, medical graduates, dental graduates, and healthcare workers.…”
Section: Discussionmentioning
confidence: 88%
“…Perceived susceptibility and perceived severity are related to negative outcomes and an individual’s perception of risk, while perceived benefits and perceived barriers relate to positive and negative consequences respectively of adopting preventive behavior [ 17 , 18 ]. Self-efficacy is a person’s belief in their ability to carry out a specific action [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%